Automatic Generation Control for Interconnected Hydro-thermal System with the help of Conventional Controllers - Vikram Kumar Kamboj; Krishan Arora; Preeti Khurana (Institute of Advanced Engineering and Science, 2012)
The Problem of Automatic Generation Control of large interconnected multi-area system is necessitated by the importance of maintenance of frequency and tie-line flows at their scheduled values. Disturbance in any part of the power system network has its effect on the frequency and tie-line power flows of the entire network. Thus, It is the responsibility of the Power system engineers to ensure that adequate power is delivered to the load reliably and economically so that nominal condition will be re-established. This Research paper aims to represents how nominal value can be achieved by close loop control of real and reactive powers generated in the controllable source of the system with the help of conventional controllers.DOI:http://dx.doi.org/10.11591/ijece.v2i4.305